Using Stop Motion Video to Improve Students' Understanding of Science Concepts: Penggunaan Video Stop Motion dalam Meningkatkan Pemahaman Konsep IPA Siswa - Anjalita Nanda Budiarti; Enik Setiyawati (Academia Open, 2023)
General background in recent years, the integration of multimedia, particularly video-based tools, has been increasingly explored in educational settings to enhance student engagement and comprehension. Specific background stop motion videos are believed to support conceptual understanding by illustrating scientific processes in a dynamic, visual format. Knowledge gap however, empirical evidence on the effectiveness of stop motion videos specifically in improving science concept comprehension in elementary education remains limited. Aims this study investigates the role of stop motion video as an instructional medium in enhancing science concept understanding among sixth-grade students. Results a quasi-experimental design was employed with two groups, an experimental group using stop motion videos and a control group using traditional methods. Post-test results indicated a statistically significant improvement in science concept comprehension in the experimental group compared to the control group, with a p-value of 0.000 < 0.05 and a t-value of 9.613 > 1.685. N-Gain analysis showed a moderate increase in the experimental group (0.3 ≤ N-Gain ≤ 0.7) compared to a low increase in the control group. Novelty this study provides empirical support for the effectiveness of stop motion videos in elementary science education, contributing new insights into multimedia learning tools. Implications the findings suggest that stop motion videos may serve as a beneficial tool for teachers to facilitate deeper understanding of complex science concepts, particularly in topics like the solar system. Highlights: Significant improvement in science concept comprehension in the experimental group. Moderate N-Gain of 0.3 ≤ N-Gain ≤ 0.7 in the experimental group. Encouragement for teachers to adopt multimedia tools for better learning outcomes. Keywords: Video, Stop Motion, Science Concepts, Elementary Education, Quasi-Experimental